The influences of stomatal size and density on rice abiotic stress resilience. Issue 6 (11th January 2023) - Caine, Robert S.; Harrison, Emily L.; Sloan, Jen; Flis, Paulina M.; Fischer, Sina; Khan, Muhammad S.; Nguyen, Phuoc Trong; Nguyen, Lang Thi; Gray, Julie E.; Croft, Holly
Summary: A warming climate coupled with reductions in water availability and rising salinity are increasingly affecting rice ( Oryza sativa ) yields. Elevated temperatures combined with vapour pressure deficit (VPD) rises are causing stomatal closure, further reducing plant productivity and cooling. It is unclear what stomatal size (SS) and stomatal density (SD) will best suit all these environmental extremes. To understand how stomatal differences contribute to rice abiotic stress resilience, we screened the stomatal characteristics of 72 traditionally bred varieties. We found significant variation in SS, SD and calculated anatomical maximal stomatal conductance ( g smax ) but did not identify any varieties with SD and g smax as low as transgenic OsEPF1oe plants. Traditionally bred varieties with high SD and small SS (resulting in higher g smax ) typically had lower biomasses, and these plants were more resilient to drought than low SD and large SS plants, which were physically larger. None of the varieties assessed were as resilient to drought or salinity as low SD OsEPF1oe transgenic plants. High SD and small SS rice displayed faster stomatal closure during increasing temperature and VPD, but photosynthesis and plant cooling were reduced. Compromises will be required when choosing rice SS and SD to tackle multiple future environmental stresses.